Hydrogen implantation optimization method of passivation interface of tellurium-cadmium-mercury (HgCdTe) infrared focal plane array device - YIN WENTING; XING WEN; YANG JIANRONG; YE ZHENHUA; LIN CHUN; HUANG JIAN; CHEN XINGGUO; DING RUIJUN; HE LI; HU XIAONING (2010)
The invention discloses a hydrogen implantation optimization method of a passivation interface of a tellurium-cadmium-mercury (HgCdTe) infrared focal plane array device and relates to a manufacturing technology of a photoelectric detector. The method adopts a technical scheme of passivation interface optimization that a photosensitive element chip with a grown cadmium telluride/zinc sulfide (CdTe/ZnS) compound medium passivation film of the HgCdTe infrared focal plane array device is directly put in a vacuum cavity for carrying out low energy plasma hydrogen implantation treatment, which effectively solves the problems of excessive unsaturated dangling bonds and interfacial charges of the HgCdTe infrared focal plane passivation interface. The method has the characteristics of simple process, quick operation, good controllability and high stability.